Determinación de calidad de agua por bioindicadores (macroinvertebrados) del río Machángara, del Distrito Metropolitano de Quito (DMQ),2021. - Chuqui Lema, Amparo Marisol (2021)
Rivers are important ecosystems to protect against pollution and other human and natural alterations, since they are a vital source for all living beings. This research was carried out in the months of April, May and June, in which the water quality of the Machángara river was determined, using bio indicators (macro invertebrates) and biological index (Biological Monitoring Working Party /Colombia, Andrean Biological Index, Index Ephemeroptera, Plecóptera, Trichoptera and the Shannon-Weaver biodiversity index); For which three sampling points were selected (P1-La Recolecta, P2- El Rosario, P3- El Guabo). According to the results achieved in the investigation, 7662 individuals of aquatic macro invertebrates were identified, the some ones that were found distributed in eighteen families; The Biological Monitoring Working Party / Colombia index in P1 and P3 Showed a Cristal Water quality and in P2 from Doubtful to Critical with respect to the Andean Biological Index and the Ephemeroptera Index, Plecóptera, Trichoptera expresses a poor water quality in the three months, since this index is calculated with orders of macro invertebrates that are perceptible to environmental variations. The Shannon – Weaver diversity index showed an average of 2.3 for the three points that is a medium diversity. According to the 9 evaluated parameters of the ICA-NSF, it was concluded that the water quality in P1 is Bad and in P2 and P3 Terrible since it appears in a range from 0 to 25. In comparison with the TULSA book VI, Annex I; Table 3. Water quality criteria for agricultural irrigation, the parameters Fecal Coliforms and Dissolved Oxygen in the three study points exceed the maximum permissible limits. With the results obtained, it was determined that the water quality is in a state of critical to terrible maintaining a relationship with the result of studies already carried out in the Machángara River, these values are affected by the presence of settlements and human activities, as well as excessive discharges that are evacuated directly to the river without any treatment.